TEKNOLOGI OLAHAN MELINJO MENJADI PRODUK MAKANAN AWET YANG ENAK DAN BERNILAI EKONOMIS TINGGI - Friska Citra Agustia; Herastuti Sri Rukmini; Rumpoko Wicaksono; Rifda Naufalin (Dinamika Journal : Pengabdian Masyarakat, 2019)
Binangun Village, Banyumas Regency is one of the centers for producing melinjo and the main processed product produced is emping melinjo. IKM Mustika Langgeng Jaya is a community that produces melinjo chips and banana chips which aims to improve the welfare of its members. However, this IKM does not know and has not yet applied processed technology based on local raw materials, the products produced are limited to emping melinjo, the packaging used is still simple and has not included a label so that short shelf life and low marketing reach. Therefore, diversification of melinjo processed products is needed, improvement of product packaging and labeling as well as the application of quality management and food safety so that products from IKM are safe for consumption. The program is carried out using counseling, training, demonstration plot or pilot practices as well as mentoring. This activity can improve the welfare of IKM Mustika Langgeng Jaya.